Bio‐Based Piezo‐ and Thermoresistive Photocurable Sensing Materials from Acrylated Epoxidized Soybean Oil. Issue 7 (15th April 2022) - Mendes‐Felipe, Cristian; Costa, Pedro; Roppolo, Ignazio; Sangermano, Marco; Lanceros‐Mendez, Senentxu
Abstract: Bio‐based photocurable polymers are increasingly in demand as environmentally friendly materials for advanced applications. Together with functional fillers, these represent a next step for the generation of functional and active smart materials, compatible with additive manufacturing technologies. Herein, acrylated epoxidized soybean oil (AESO) mixed with different amounts of reduced graphene oxide (rGO) up to 6 wt% in order to obtain UV‐curable piezoresistive and thermoresistive materials, is reported. It is shown that the addition of rGO to AESO hinders the curing process, but always maintains double bond conversions higher than 50%. Composites are characterized by a good dispersion of micrometric filler clusters. Further, the thermal stabilities are close to 300 °C and crosslinking degrees are above 1.75 mmol cm –3 . The Young modulus of the composites decreases with the addition of the rGO fillers, in particular for the higher filler contents, and electrical conductivities up to 0.13 S m –1 are obtained for the composites with the highest rGO content. UV‐curable composites with piezoresistive and thermoresistive responses suitable for applications are thus obtained, characterized by gauge factors around 26 for deformations up to 2% and maximum thermoresistive sensitivity of S = 0.43, values similar to the values obtained for petroleum‐based materials. Abstract : This work reports on photocurable bio‐based composite materials obtained by the combination of acrylated epoxidized soybean oil and reduced graphene oxide. The addition of the fillers leads to a large increase on the electrical conductivity at the percolation threshold, as well as to piezoresistive and thermoresistive responses compatible with the application of the photocurable bio‐based materials as sensing materials.